Alzheimer's Patient Organizations' Role in Enabling Citizenship Projects: A Comparison of the USA, Germany, and the UK - Mitra, Sayani; Schicktanz, Silke (Frontiers in Sociology, 2020)
This paper examines how Alzheimer’s disease (AD) patient support organizations (POs) located in diverse healthcare regimes enable patients to claim and construct their rights as citizens. Since citizenship rights of people with AD are debated widely, it is important to recognise the role of POs in enabling people to construct citizenship identities. This paper thus examines the factors that shape the citizenship projects of the AD POs. Since collective health-related behaviour changes in line with national differences, we compare the biggest AD POs in three starkly distinct healthcare regimes: the Alzheimer’s Association in the US (ALZ), the Deutsche Alzheimer Gesellschaft (German Alzheimer’s Association) in Germany (DAG) and Alzheimer’s Society in the UK (AS), to examine how distinct health policy contexts shape their citizenship projects. Based on our website analysis of the three POs and other related secondary documents, we argue that the way each POs work towards enabling its members to claim rights and assume responsibilities depend upon the nature of healthcare funding and resource allocation for AD care. Since AD involves long-term care, the ways in which the three POs enable the people with AD to secure their care expenses set apart the nature of citizenships enactments.